2020
DOI: 10.1111/cas.14681
|View full text |Cite
|
Sign up to set email alerts
|

Tislelizumab in Asian patients with previously treated locally advanced or metastatic urothelial carcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 27 publications
4
99
0
Order By: Relevance
“…It remains to be investigated whether NTX or its analogues combined with DOX or CIS can enhance the anti-tumor effect, promote the extrusion of drugs into extracellular space by drug efflux pumps, and even delay the development of drug resistance in UBC without significantly increasing toxicity. We also noticed that previous clinical trials focused on the therapeutic effect of NTX (APL-1202) on NMIBC, while a multicenter study (NCT04813107, Phase I/II) on the combination of NTX with tislelizumab, a monoclonal antibody against programmed cell death protein 1 (PD-1) 45 will be started to assess their efficacy and safety in cisplatin-ineligible MIBC patients. Our previous work found that NTX decreases the levels of myeloid-derived suppressor cells (MDSCs) in UBC-bearing murine model 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be investigated whether NTX or its analogues combined with DOX or CIS can enhance the anti-tumor effect, promote the extrusion of drugs into extracellular space by drug efflux pumps, and even delay the development of drug resistance in UBC without significantly increasing toxicity. We also noticed that previous clinical trials focused on the therapeutic effect of NTX (APL-1202) on NMIBC, while a multicenter study (NCT04813107, Phase I/II) on the combination of NTX with tislelizumab, a monoclonal antibody against programmed cell death protein 1 (PD-1) 45 will be started to assess their efficacy and safety in cisplatin-ineligible MIBC patients. Our previous work found that NTX decreases the levels of myeloid-derived suppressor cells (MDSCs) in UBC-bearing murine model 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of urothelial cancer, anti-PD-1/PD-L1 has become the first-line treatment option [ 177 ]. A retrospective analysis of 270 patients in 10 European institutions treated with ICIs indicated that bone metastases were associated with poor prognosis [ 178 ].…”
Section: Clinical Effects Of Immune Checkpoint Inhibitors To Bone Metastasismentioning
confidence: 99%
“…In another study, 113 Asian patients with local progression or distant metastasis received PD-1 inhibitor tislelizumab treatment. The ORR was 24%, while the impact on bone metastasis was not specifically described [ 177 ].…”
Section: Clinical Effects Of Immune Checkpoint Inhibitors To Bone Metastasismentioning
confidence: 99%
“…In the treatment of classical Hodgkin lymphoma, tislelizumab was well tolerated with a high ORR of 87.1% ( Song et al, 2019a ). It also provided an OS of 9.8 months in patients with UC ( Ye et al, 2021 ). Those results led to its approval for classical Hodgkin lymphoma and UC in China.…”
Section: Clinical Use Efficacy and Safetymentioning
confidence: 99%